دور التحفيز في تحسين أداء العاملين دراسة حالة المؤسسة الوكالة الولائية للتشغيل فرع الوادي وقمار - قروي عبد الجبار; لعيس عبد المولى; قيدوس لخضر (جامعة الوادي University of Eloued, 2025)
"تهدف هذه الدراسة إلى إبراز دور التحفيز في تحسين أداء العاملين، مع التركيز على حالة المؤسسة الوكالة الولائية للتشغيل فرع الوادي وقمار. اعتمدت الدراسة المنهج الوصفي لوصف الظاهرة المدروسة من خلال عرض مختلف المفاهيم، بالإضافة إلى المنهج التحليلي لتعقيب على ما تم وصفه وتحليل الأشكال والجداول الواردة، خاصة المتعلقة بالبيانات التطبيقية. يتكون مجتمع الدراسة من مجموع الموظفين بالفرع الولائي لوكالة التشغيل، والذي يضم 30 موظفًا. تم معالجة المعطيات باستخدام برنامج SPSS v.25، حيث تم تحويلها إلى جداول ورسمها بيانياً لتسهيل عملية الملاحظة والتحليل. خلصت النتائج إلى وجود أثر إيجابي معنوي لكل من الحوافز المادية والمعنوية على أداء العاملين. وقد تم قبول الفرضية الفرعية الأولى التي تنص على وجود علاقة ذات دلالة إحصائية عند مستوى الدلالة 0.05≥α بين الحوافز المادية وأداء العاملين بالمؤسسة. كما تم قبول الفرضية الفرعية الثانية التي تشير إلى وجود علاقة ذات دلالة إحصائية عند نفس المستوى بين الحوافز المعنوية وأداء العاملين. تؤكد هذه النتائج على أهمية التحفيز كأداة فعالة لتحسين الأداء الوظيفي، مما يسهم في تحقيق الأهداف المؤسسية وزيادة رضا الموظفين. "This study addresses the role of motivation in enhancing employee performance, focusing on the case of the Wilaya Employment Agency branch in El-Oued and Guemar. The study employed a descriptive approach to describe the phenomenon under investigation by presenting various concepts, along with an analytical approach to discuss and analyze the figures and tables presented, particularly those related to the applied data. The study population consisted of all employees at the Wilaya Employment Agency branch, totaling 35 employees. Data was processed using SPSS v.25, where it was transformed into tables and represented graphically to facilitate observation and analysis. The findings revealed a positive significant effect of both material and moral incentives on employee performance. The first sub-hypothesis was accepted, indicating a statistically significant relationship at the significance level of 0.05≥α between material incentives and employee performance at the agency. The second sub-hypothesis was also accepted, indicating a statistically significant relationship at the same level between moral incentives and employee performance. These results emphasize the importance of motivation as an effective tool for improving job performance, contributing to the achievement of institutional goals and increasing employee satisfaction.
ماستر
Keywords: تحفيز – أداء - أداء العاملين; Motivation – Performance – Employee Performance